Penggunaan Permainan dalam Pembelajaran IPS di Sekolah Dasar - - Rahmatina (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2007)
Abstract: The purpose of the study is to describe the importance of games in learning social studies in the elementary school. There are some games that can be used in learning process, i.e. concept classification or topics of learning, searching area location in the map, puzzles, and word-puzzle. Through using games in learning, students can improve their learning outcomes.